2022
DOI: 10.1002/aic.17612
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production via chemical looping dry reforming of methane: Process modeling and systems analysis

Abstract: The present study presents and analyses a family of "chemical looping dry reforming" (CLDR) processes that produce inherently separated syngas (H 2 and CO) streams via a combination of methane cracking in a "cracker reactor" and the Boudouard reaction (i.e., conversion of the formed carbon with CO 2 to CO) in a "CO 2 reactor," and then further maximize the H 2 yield via conversion of the produced CO via water-gas-shift.Remaining CO 2 emissions are minimized via CO 2 capture and sequestration. Four different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The Fe 2p spectrum exhibits two contributions, Fe 2p 3/2 and Fe 2p 1/2 , located at approximately 710.5 and 724.2 eV, respectively, accompanied by the satellite peaks at about 718.0 and 733.1 eV. ,, Furthermore, the Fe 2p 3/2 spectra can be divided into the peaks at around 710.0 and 712.1 eV, corresponding to the Fe 2+ 2p 3/2 and Fe 3+ 2p 3/2 , respectively. Similarly, the peaks at around 723.7 and 725.8 eV can be ascribed to Fe 2+ 2p 1/2 and Fe 3+ 2p 1/2 , respectively, in the Fe 2p 1/2 spectra . As shown in Table , based on the peak fitting results, the relative content of Fe 2+ is about 45%, with the remaining Fe in the form of Fe 3+ .…”
Section: Resultsmentioning
confidence: 78%
“…The Fe 2p spectrum exhibits two contributions, Fe 2p 3/2 and Fe 2p 1/2 , located at approximately 710.5 and 724.2 eV, respectively, accompanied by the satellite peaks at about 718.0 and 733.1 eV. ,, Furthermore, the Fe 2p 3/2 spectra can be divided into the peaks at around 710.0 and 712.1 eV, corresponding to the Fe 2+ 2p 3/2 and Fe 3+ 2p 3/2 , respectively. Similarly, the peaks at around 723.7 and 725.8 eV can be ascribed to Fe 2+ 2p 1/2 and Fe 3+ 2p 1/2 , respectively, in the Fe 2p 1/2 spectra . As shown in Table , based on the peak fitting results, the relative content of Fe 2+ is about 45%, with the remaining Fe in the form of Fe 3+ .…”
Section: Resultsmentioning
confidence: 78%
“…Several analyses have found that future energy for CO 2 capture (in terms of the parasitic load (MJ/kg-CO 2 ) for the power plant) is related to the developments in capture technologies. IECM currently allows simulation of chemical looping capture, which is widely considered as a benchmark for an improved technology. , IECM models chemical looping capture based on the design provided by their publications, which involves a heat recovery steam generator. These processes are found to be thermodynamically much more efficient than postcombustion incumbents.…”
Section: Methodsmentioning
confidence: 99%
“…The syngas is purified using a monoethanolamine (MEA)-based CO 2 capture process that separates H 2 O and CO 2 in raw syngas. 15 The waste heat from raw syngas and flue gas is recovered to preheat air and generate steam. Any remaining low-grade heat is utilized in generating electricity through a steam turbine.…”
Section: Process Configuration/designmentioning
confidence: 99%
“…12,13 Chemical looping gasification (CLG) has emerged as a promising gasification technology, garnering significant attention from researchers. 14,15 A schematic of a typical CLG process is illustrated in Figure 1, where two interconnected fluidized bed reactors serve as an air reactor (AR) and a fuel reactor (FR). The fuel is mixed with an oxygen carrier that provides the necessary lattice oxygen for fuel gasification in the FR.…”
mentioning
confidence: 99%